Emodin attenuates severe acute pancreatitis-associated acute lung injury by suppressing pancreatic exosome-mediated alveolar macrophage activation - Qian Hu; Jiaqi Yao; Xiajia Wu; Juan Li; Guixiang Li; Wenfu Tang; Jingping Liu; Meihua Wan (Acta Pharmaceutica Sinica B, 2022)
Severe acute pancreatitis-associated acute lung injury (SAP-ALI) is a serious disease associated with high mortality. Emodin has been applied to alleviate SAP-ALI; however, the mechanism remains unclear. We report that the therapeutic role of emodin in attenuating SAP-ALI is partly dependent on an exosomal mechanism. SAP rats had increased levels of plasma exosomes with altered protein contents compared to the sham rats. These infused plasma exosomes tended to accumulate in the lungs and promoted the hyper-activation of alveolar macrophages and inflammatory damage. Conversely, emodin treatment decreased the plasma/pancreatic exosome levels in the SAP rats. Emodin-primed exosomes showed less pro-inflammatory effects in alveolar macrophages and lung tissues than SAP exosomes. In detail, emodin-primed exosomes suppressed the NF-κB pathway to reduce the activation of alveolar macrophage and ameliorate lung inflammation by regulating PPARγ pathway, while these effects were amplified/abolished by PPARγ agonist/antagonist. Blockage of pancreatic acinar cell exosome biogenesis also exhibited suppression of alveolar macrophage activation and reduction of lung inflammation. This study suggests a vital role of exosomes in participating inflammation-associated organ-injury, and indicates emodin can attenuate SAP-ALI by reducing the pancreatic exosome-mediated alveolar macrophage activation.